Social representations theory: An approach to studying translators’ socio-cognitive processes - Hokkanen, Sari (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Social Representations Theory provides a comprehensive theoretical model for researching translators’ socio-cognitive processes. Developed in social psychology in the 1960s, the theory offers an integrative view of both individual and social processes in the construction and re-construction of knowledge. It draws attention to embodied meaning-making and the effect of material surroundings in perpetuating and disseminating social representations. Importantly, Social Representations Theory does not see representations as individual, solely conscious, or static mental constructions but as dynamic social–psychological phenomena that are enacted in discourse and social interaction. This article discusses Social Representations Theory as an approach to the empirical study of translators’ cognitive processes. Introducing the main concepts of the theory and using translators’ conceptualizations of source-text authors and target-text readers as an example, the article suggests avenues for using the theory in Cognitive Translation Studies.